2018
DOI: 10.1073/pnas.1722491115
|View full text |Cite
|
Sign up to set email alerts
|

Reporter–nanobody fusions (RANbodies) as versatile, small, sensitive immunohistochemical reagents

Abstract: Sensitive and specific antibodies are essential for detecting molecules in cells and tissues. However, currently used polyclonal and monoclonal antibodies are often less specific than desired, difficult to produce, and available in limited quantities. A promising recent approach to circumvent these limitations is to employ chemically defined antigen-combining domains called "nanobodies," derived from single-chain camelid antibodies. Here, we used nanobodies to prepare sensitive unimolecular detection reagents … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 39 publications
(39 reference statements)
0
43
0
Order By: Relevance
“…Nanobodies have arisen as a substitute to conventional antibodies and show great potential when used as tools in the diagnostic field [45][46][47][48]. One of the main advantages of nanobodies is that several tags can be fused in their tertiary structure by recombinant technology [9][10][11]13]. Based on this advantage, PPV-VP2 specific nanobody-HRP and -EGFP fusions were used for the first time as probes to develop immunoassays for PPV detection in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanobodies have arisen as a substitute to conventional antibodies and show great potential when used as tools in the diagnostic field [45][46][47][48]. One of the main advantages of nanobodies is that several tags can be fused in their tertiary structure by recombinant technology [9][10][11]13]. Based on this advantage, PPV-VP2 specific nanobody-HRP and -EGFP fusions were used for the first time as probes to develop immunoassays for PPV detection in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Because nanobodies contain only one ∼ 130 amino acid variable domain, they can be simply derivatised by coupling to reporters or dyes. For example, one study designed a reporter-nanobody fusion (RANbody) platform, in which RANbody was used in immunohistochemical detection [9]. Other works have reported the application of nanobody-HRP, EGFP, or nano-luciferase fusions derived from nanobodies to develop detection assays, label cells and tissues, and for other purposes [10][11][12][13].…”
mentioning
confidence: 99%
“…It has been suggested that nAbs preferentially bind to target proteins via a convex paratope (Wurch et al, 2012), which could contribute to the inability of the nAbs against the targets with the exception of Homer1 to detect aldehyde-fixed and/or denatured target proteins. While nAbs have widespread use in binding to native protein, which enhances their utility as chaperones for crystallography , some generated against GFP and other proteins have been used as immunolabels for immunohistochemistry (Fang et al, 2018;Yamagata and Sanes, 2018) and immunoblots (Bruce and McNaughton, 2017) In summary, we have generated a series of validated nAbs against neuronal proteins selectively expressed in specific subcellular compartments in brain neurons. These nAbs represent a valuable toolbox of reagents available to the neuroscience community for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
“…Each target has its advantages and disadvantages depending on the model system and experimental question at hand. Nbs of either persuasion can be delivered into cells or animals by genomic engineering; the Nb cDNA sequences are placed under the control of cell-specific, inducible, or ubiquitous reporter sequences (Panza et al, 2015; Rothbauer et al, 2006; Yamagata & Sanes, 2018). In model organisms lacking established transgenic lines like the sea urchin, in vivo Nb expression can be easily encoded in F 0 by using mRNA overexpression (Fig.…”
Section: Introductionmentioning
confidence: 99%